KANDUNGAN NUTRISI KASGOT LARVA LALAT TENTARA HITAM (Hermetia illucensi) SEBAGAI PUPUK ORGANIK - Heny Agustin; Warid Warid; Illa Muliani Musadik (BPFP Universitas Bengkulu, 2023)
[NUTRITIONAL CONTENT OF BLACK SOLDIER FLY LARVAE (Hermetia illucensi) FRASS AS ORGANIC FERTILIZER]. Nowadays, maggots or Black Soldier Fly (BSF) larvae are widely used as organic waste decomposers. The use of maggot as a macro-organism waste decomposer is considered an innovation in processing waste. Maggot farming produces residue which is called Black Soldier Fly Larvae Frass (BSFF). BSFF is called organic solid fertilizer and can optimize growth because it contains various nutrient flows needed for plants. Therefore, the objective of this study was to assess the nutritional content of BSF larvae reared in the waste of rice, fruits, vegetables, and their mixture. Within this aim, it was conducted a laboratory experiment using four treatments of BSFF (the waste of rice, fruits, vegetables, and their mixture) research was conducted from March to June 2022 at the Experimental Garden and Integrated Laboratory of Trilogi University, Jakarta, with the Seameo Biotrop Laboratory, Tajur-Bogor, West Java. BSFF nutrient content was measured by the organic fertilizer test kit (PUPO) and standard laboratory procedure. According to the result of the PUPO or laboratory test, it was found that BSFF from organic waste harvested two weeks has fulfilled the standard from Permentan 2019, especially on the treatment of giving waste of rice, vegetables, or fruits with pH criteria between 4-9, C organic more than 15%, ratio C/N less than 25, the total value NPK nutrient more than 2% and Fe was found to be less than 500 mg/kg.